THE INNOVATIVE APPROACH IN LEXICAL UNITS ON JOURNALISM - Xusanova, Yulduz (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The present paper aims at the analysis of lexical innovations in the sphere of journalism. For achieving them a set of procedures were fulfilled to show the peculiarities of journalism innovations and a number of methods were used. The descriptive method helped to analyze the selected words and word combinations, component analysis proved valuable to regard the semantic structure or the vocabulary. Word building classification was helpful in the defining the predominant kind of word formation in the units. Calculations gave the possibility to state the number of examples in the dictionaries, define the major and minor types of word formation of innovations.